Hygiene Sanitasi dan Keberadaan Bakteri Escherichia Coli pada Semanggi sebagai Jajanan Tradisional Surabaya (Studi Di Kampoeng X, Kecamatan Y, Surabaya): Hygiene Sanitation and Escherichia Coli Bacteria on Clover Leaves as Surabaya Traditional Culinary (Study in Kampoeng X, Y District, Surabaya) - Anita Dewi Moelyaningrum; Resty Ayu Permatasari; Ninna Rohmawati (Universitas Airlangga, 2023)
Backgrounds: Clover food, or Semantic, is one of the traditional Surabaya culinary delights and is still the most favorable for various communities and tourists for its unique taste. Clover food is one of the potential foods to be contaminated by microbes because it does not implement hygiene and sanitation to handle it. Objectives: This research was conducted to analyze the hygiene sanitation and the Escherichia Coli bacteria at clover food Surabaya, Indonesia Methods: This type of research was descriptive with Interviews, observation, and laboratory tests collected data. The total samples examined were 32 respondents and 64 clover samples consisting of 32 clovers and 32 seasonings. Results: Almost all of the respondents had a higher level of knowledge (93.8%), had applied personal hygiene in the excellent category (59.4%), and had applied sanitation of food processing that was well-rated (87.5%). According to the lab, there were two positive samples of E. Coli. Conclusions: Almost all respondents had not applied appropriate personal hygiene, and E. Coli bacteria were still found in the clover food. One was found in highly-educated respondents who applied food processing sanitation well.